Effects of vitamin D group steroids on mesomorphic phase states of cholesteric sensor materials - Panikarskaya, V.D.; Kasyan, N.A.; Lisetski, L.N.; Terenetskaya, I.P. (Functional Materials, 2005)
Effects of non-mesogenic provitamin D and vitamin D upon thermal stability of cholesteric and smectic-A phases formed by mixtures of cholesterol esters have been studied. Widening of DSC and selective reflection peaks were noted for higher (>5 %) concentrations of provitamin D, which were accompanied by deviations from linearity of concentration dependences of cholesteric - isotropic and cholesteric - smectic transition temperatures. The respective limiting concentrations for provitamins D₂ and D₃ in different matrices correlate with eutectic concentration values calculated using Schroeder-van Laar equations. The results obtained present a physico-chemical basis for development of optimized sensor materials for bioequivalent UV detectors that would meet contradictory requirements of high sensitivity and high thermodynamic stability.